2020
DOI: 10.3390/vaccines8020218
|View full text |Cite
|
Sign up to set email alerts
|

Are the Objectives Proposed by the WHO for Routine Measles Vaccination Coverage and Population Measles Immunity Sufficient to Achieve Measles Elimination from Europe?

Abstract: Background: The World Health Organization (WHO) proposed two-dose measles vaccination coverage of at least 95% of the population and percentages of measles immunity in the population of 85%−95% in order to achieve measles elimination in Europe. The objectives of this study were: (1) to determine the measles vaccination coverage required to establish herd immunity against measles viruses with basic reproduction numbers (Ro) ranging from 6 to 60, and (2) to assess whether the objectives proposed by the WHO are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
0
31
1
Order By: Relevance
“…Measles vaccination with the two-dose measles vaccine can reduce measles incidence by direct and indirect protection in the target vaccination population and by indirect herd immunity protection in other population groups. Another study found that to meet the goal of measles elimination in Europe, it is necessary to achieve percentages of two-dose measles vaccination coverage of at least 97% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Measles vaccination with the two-dose measles vaccine can reduce measles incidence by direct and indirect protection in the target vaccination population and by indirect herd immunity protection in other population groups. Another study found that to meet the goal of measles elimination in Europe, it is necessary to achieve percentages of two-dose measles vaccination coverage of at least 97% [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mean percentages of vaccination coverage with one and two doses of measles vaccine and one, two, and three doses of DTP vaccine in different regions of WHO were determined from the vaccination coverage with one and two doses of measles vaccine and one, two, and three doses of DTP vaccine in countries of the region (phase 2 of the analysis). Routine measles vaccination is based on two doses of a measles-containing vaccine (measles-rubella-mumps (MMR) vaccine) administered at 12–15 months (MCV1) and 3 years of age (MCV2) [ 13 , 20 , 21 ]. The percentages of vaccination coverage with MCV1 and MCV2 reported by different countries to the WHO–UNICEF global and regional immunization information system are provided for the nationally recommended age [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2015 the Hellenic Centre for Disease Control and Prevention (HCDCP) informed the Greek physicians about the risk of an upcoming measles outbreak and urged them to increase the vaccination rate with MMR, targeting vaccine coverage of ≥95%. According to recently published data [ 17 ], to eliminate measles in Europe, it is necessary to succeed percentages of complete vaccination coverage of at least 97% and measles immunity levels in children aged 1−9 years of at least 95%. In Greece, the percentage of one dose vaccine coverage with MMR in preschool children aged 2–3 years is deemed satisfactory, reaching 97.3% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%